Methodological Foundations For The Application of The Socio-Ethical Views of Timurid-Era Thinkers In New Uzbekistan - Damirovich, Mustayev (Indonesian Journal Publisher, 2025)
The article investigates the theoretical and methodological underpinnings for examining the socio-ethical views of Timurid philosophers, the hermeneutic basis of these viewpoints, and the pedagogical implications of these views in the context of New Uzbekistan. Furthermore, the methodological grounds for applying Timurid-era intellectuals’ socio-ethical views to New Uzbekistan have been examined. Despite the fact that several scientific studies have been conducted in the history of philosophy on the study of the science and culture of the Timurid dynasty, the essence of the socio-moral views of the thinkers of the Timurid era has not been specifically studied from the perspective of the present day. Therefore, in this article, a comprehensive study of the socio-moral views of the thinkers of the Timurid era based on a hermeneutic approach is of urgent scientific importance.